2015
DOI: 10.5194/amt-8-225-2015
|View full text |Cite
|
Sign up to set email alerts
|

Case study on complex sporadic E layers observed by GPS radio occultations

Abstract: Abstract. The occurrence of sporadic E (E s ) layers has been a hot scientific topic for a long time. The GNSS (global navigation satellite system)-based radio occultation (RO) has proven to be a powerful technique for detecting the global E s layers. In this paper, we focus on some cases of complex E s layers based on the RO data from multiple missions processed in UCAR/CDAAC (University Corporation for Atmospheric Research (UCAR) the Constellation Observing System for Meteorology, Ionosphere, and Climate (CO… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
68
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(72 citation statements)
references
References 46 publications
(94 reference statements)
2
68
0
2
Order By: Relevance
“…Maeda and Heki () has pointed out that records by multiple ionosondes in Japan separated by more than 1,000 km often show simultaneous occurrences of E s (enhancement of f o E s ), which were not clear whether to represent the appearance of a single large E s structure or just a simultaneous appearance of multiple E s structures. Yue et al () also reported simultaneous E s occurrence in a broad region with multiple GNSS RO observations. In addition, we observed multiple E s patches lined up in the same azimuth, thus seemingly to be an extra‐large one band‐like structure.…”
Section: Case Studymentioning
confidence: 89%
See 1 more Smart Citation
“…Maeda and Heki () has pointed out that records by multiple ionosondes in Japan separated by more than 1,000 km often show simultaneous occurrences of E s (enhancement of f o E s ), which were not clear whether to represent the appearance of a single large E s structure or just a simultaneous appearance of multiple E s structures. Yue et al () also reported simultaneous E s occurrence in a broad region with multiple GNSS RO observations. In addition, we observed multiple E s patches lined up in the same azimuth, thus seemingly to be an extra‐large one band‐like structure.…”
Section: Case Studymentioning
confidence: 89%
“…However, it also has some problems such as lower detection threshold (Haldoupis, ). Since the advent of Global Navigation Satellite Systems (GNSS) radio occultation (RO) technique, it has been widely used in E s detection (e.g., Arras et al, ; Hocke et al, ; Wu et al, ; Yue et al, , ). Either the signal‐to‐noise ratio fluctuation or the electron density enhancement could be used to identify E s occurrence in RO signal (Yue et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, techniques for Es observations have remarkably enhanced. The GNSS radio occultation (RO) observation (satellite‐to‐satellite communication links) provides an ideal geometry with a significantly improved spatial and temporal vertical resolution, which has been used to study the Es layer structure (e.g., Arras et al, ; Chen et al, ; Liu et al, ; Wickert et al, ; Wu et al, ; Yue et al, ; Zeng & Sokolovskiy, ). On the other hand, ground‐based Global Positioning Systems (GPS) receivers provide an adequate technique to observe the scintillation of radio waves in Earth's ionosphere (Pi et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…and Devasia [6] proposed theories to explain the formation of Es at equatorial latitudes, which are based on the horizontal convergence of ions. Furthermore, in the high latitude region, the occurrence of Es is more significantly influenced by the local electric field rather than the wind shear due to the geomagnetic field difference [7,8].…”
Section: Introductionmentioning
confidence: 99%